Theoretical considerations over trust: relevant aspects for organizational behaviour - Costa, Ana Cristina (1999)
The concept of trust has been studied by a large number of scholars from various scientific backgrounds. Trust has showed to play a major role in social relations, organizations, political systems, economic transactions and even in human-computer interaction. Many scholars appear united with respect to the importance of trust as a “public good”, necessary for the success of many economic transactions. Lewis and Weigert (1985, p.968) suggest that “trust is indispensable in social relationships”. Zucker (1986, p.56) followed with the statement that trust is “vital for the maintenance of cooperation in society and necessary as grounds for even the most routine, everyday interaction.” Luhmann (1980, p.4) goes further by arguing that trust is necessary to reduce complexity in the social systems, “absence of trust would prevent him (individual) from getting up in the morning”. Although the importance of trust has been acknowledged, its study remains problematic for several reasons. Since trust is a basic factor for the understanding of human conduct, its study is not restricted to a particular level of analysis. In the literature we find trust related to individuals, interpersonal relations, organizational structures, economic transactions and societies as a whole. In these contexts, several definitions have been proposed causing considerable confusion among researchers. However the earlier work has not been wasted. Each definition proposed, even with the limitations of its own approach, provides new information, adds insight and understanding to the meaning of trust. The fact that trust can be studied at different levels (individuals, groups and societies) and in different contexts, points out the relevancy of a multilevel analysis as well a simultaneous consideration of the context, in order to develop a meaningful framework for the study of trust (Rousseau, Stikin, Burt and Carmer, 1998). DOI: http://dx.doi.org/10.17575/rpsicol.v13i1/2.561